2019
DOI: 10.4103/ijpsym.ijpsym_569_17
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Temporal Variation of Suicide in India, 2006-2015: An Investigation of Factors Associated with Suicide Risk Difference across States/Union Territories

Abstract: Background: In India, about 130,000 people died by suicide in the year 2015. It is important to understand the variation of suicide across different parts of India and the trend of suicide rates over the years. The objectives of this study were to determine whether suicide rates in India showed temporal variation in the last decade and to determine whether suicide rates in India showed geographical variation across different states and union territories (UTs). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In 1897, Durkheim5 reported that a religious belief and affiliation protected against suicide. More than a century later, Ramamurthy and Thilakan14 made the same observation. It would not be appropriate for authorities to encourage religious participation as a means of protecting against suicide.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…In 1897, Durkheim5 reported that a religious belief and affiliation protected against suicide. More than a century later, Ramamurthy and Thilakan14 made the same observation. It would not be appropriate for authorities to encourage religious participation as a means of protecting against suicide.…”
mentioning
confidence: 60%
“…In comparison with high income countries, they found India had a larger rate of female suicides, and mental illness was less commonly present. Ramamurthy and Thilakan14 looked at geographical and temporal rate variation across India in the decade 2006-2015. For the whole country, there was no variation in rate over time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research is not so clear. Although high suicide rates have been reported in Finland, Ireland and Italy in the summer, this model is much less expressed or even absent in studies conducted in England and Wales, Australia and New Zealand, Singapore and Switzerland [26,27,28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 96%
“…However, our results from the study years (i.e., 2016 to 2020) were inconsistent with the trend noted above. In many other countries, studies have noted differences in seasonal trends based on age and sex, with variations depending on the time and country of the study [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Further research is necessary to determine whether the difference between the current and prior studies is due to a change in the seasonal trend of suicide attempts in Korea or differences according to age groups.…”
Section: Discussionmentioning
confidence: 99%